EGFR and ERBB2 exon 20 insertion/duplication in advanced non–small cell lung cancer: genomic profiling and clinicopathologic features - Sompallae, Ramakrishna R.; Dundar, Bilge; Guseva, Natalya V.; Bossler, Aaron D.; Ma, Deqin (Frontiers in Oncology, 2023)
Background Exon 20 (ex20) in-frame insertions or duplications (ins/dup) in epidermal growth factor receptor (EGFR) and its analog erb-b2 receptor tyrosine kinase 2 (ERBB2) are each detected in 1.5% of non–small cell lung cancer (NSCLC). Unlike EGFR p.L858R or ex19 deletions, ex20 ins/dup is associated with de novo resistance to classic EGFR inhibitors, lack of response to immune checkpoint inhibitors, and poor prognosis. US Food and Drug Administration has approved mobocertinib and amivantamab for targeting tumors with this aberration, but the number of comprehensive studies on ex20 ins/dup NSCLC is limited. We identified 18 cases of NSCLCs with EGFR/ERBB2 ex20 ins/dup and correlated the findings with clinical and morphologic information including programed death-ligand 1 (PD-L1) expression. Methods A total of 536 NSCLC cases tested at our institution between 2014 and 2023 were reviewed. A custom-designed 214-gene next-generation sequencing panel was used for detecting DNA variants, and the FusionPlex CTL panel (ArcherDx) was used for the detection of fusion transcripts from formalin-fixed, paraffin-embedded tissue. Immunohistochemistry (IHC)for PD-L1 was performed using 22C3 or E1L3N clones. Results Nine EGFR and nine ERBB2 ex20 ins/dup variants were identified from an equal number of men and women, 14 were non- or light smokers, and 15 had stage IV disease. All 18 cases were adenocarcinomas. Seven of the 11 cases with available primary tumors had acinar predominant pattern, two had lepidic predominant pattern, and the remainder had papillary (one case) and mucinous (one case) patterns. Ex20 ins/dup variants were heterogenous in-frame one to four amino acids spanning A767–V774 in EGFR and Y772–P780 in ERBB2 and were clustered in the loop following the C-helix and α C-helix. Twelve cases (67%) had co-existing TP53 variants. Copy number variation in CDK4 amplification was identified in one case. No fusion or microsatellite instability was identified in any case. PD-L1 was positive in two cases, low positive in four cases, and negative in 11 cases. Conclusions NSCLCs harboring EGFR/ERBB2 ex20 ins/dup are rare and tend to be acinar predominant, negative for PD-L1, more frequent in non- or light smokers, and mutually exclusive with other driver mutations in NSCLC. The correlation of different EGFR/ERBB2 ex20 ins/dup variants and co-existing mutations with response to targeted therapy and the possibility of developing resistant mutations after mobocertinib treatment warrants further investigation.